Design of a pump-as-turbine microhydro system for an abalone farm - Teuteberg, B. H. (Stellenbosch : University of Stellenbosch, 2010)
ENGLISH ABSTRACT: This document details the design process of a 97 kW microhydro system for Roman Bay Sea Farm in Gansbaai in the Western Cape Province of South Africa. It contains a literature study of microhydro power, with a focus on the use of Pump-as-Turbine technology and direct-drive systems. The literature study leads to several possible concepts for the project, which are then evaluated and the most suitable design is found to be a reverse running pump that powers a different pump through a direct drive system. Experimental data from KSB is used to test the accuracy of various correlations that can be used to generate turbine-mode operation curves from pump curves. The final design parameters for the complete system are then determined, and presented along with a cost benefit analysis.